Wild ride - Calabrese, Keith (Scholastic Press, 2022)
Seventh-grader Charley Decker's mother is on vacation with her boyfriend, and Charley plans to spend the weekend watching movies with her best friends Wade and Oona and her older brother, Greg; but Greg has a date and takes their mother's boyfriend's expensive, rare automobile, than manages to get it towed; Charley and her friends hatch a plan to get the car back--but things go seriously wrong when they discover somebody called Mitch hiding from a pair of scary dudes in the trunk of the car, and the three friends find themselves on the wildest ride of their lives.